Information technology, mathematics achievement and educational equity in developed economies. Issue 4 (8th August 2017) - Tan, Cheng Yong; Hew, Khe Foon
Abstract: The present study examined how access to home and school IT resources impacted student mathematics achievement. Data comprised 144, 395 secondary school students from 7, 308 schools in 22 developed economies who participated in the Programme for International Student Assessment (PISA) 2012. Results of hierarchical linear modelling showed that after controlling for student and school covariates, student achievement benefited from their access to home IT resources (main effect), and from the access to both home IT resources and highly educated mothers (interactive effect). Furthermore, IT resource shortages in school had a detrimental impact on student achievement (main effect), and the shortage accentuated the negative effects of school shortage in qualified teachers on achievement (interactive effect). Lastly, the results showed that students with less home academic and cultural resources were more impacted by IT resource access when compared to peers from advantaged families.